Application of the generative learning model assisted by e-modules and PhET simulations to improve students' problem-solving skills on straight-line motion material for Grade XI at SMA YPK - Agnes Selvia Putri; Haratua Tiur Maria Silitonga; Firdaus Firdaus (Jurnal Pendidikan Informatika dan Sains, 2026)
This study aims to determine the effectiveness of implementing a generative learning model assisted by e-modules with PhET simulation in improving students' problem-solving skills on the topic of straight-line motion in Grade XI of SMA YPK. The researcher employed a quantitative approach with a pre-experimental research design, specifically the one-group pretest-posttest design. The sample in this study consisted of all 12 Grade XI students from SMA YPK Pontianak. Data collection techniques included tests and observations. The tests administered were a pre-test and a post-test. The instruments used in this study were the test instruments and a teaching module containing Student Worksheets (Lembar Kerja Peserta Didik) and a Lesson Plan (Rencana Pelaksanaan Pembelajaran). Data analysis in this study utilized the Wilcoxon Signed Rank Test to determine the mean difference between the pretest and posttest scores, and the N-Gain test was used to determine the magnitude of the learning model's effectiveness. The results of the Wilcoxon Signed Rank Test showed an Asymp. Sig. (2-tailed) value of 0.002 (< 0.05), indicating that there is a significant difference between the pretest and posttest scores. This means that the treatment given had a significant effect on improving students’ problem-solving skills. This finding is supported by the N-Gain calculation, which produced an average N-Gain value of 0.73, indicating that the effectiveness falls into the high category.